(untitled) (Revista Internacional de Ciencias Sociales, 2023)
Particularly in the early years of life, oral health education is crucial in determining an individual’s general well-being. The need of including comprehensive oral health instruction in the school curriculum is examined in this essay as a wise social investment. The study explores the many advantages of this kind of program, highlighting how it might improve students’ oral health conditions as well as their general health results. The abstract demonstrates the beneficial effects of oral health education on preventing dental problems, enhancing general health literacy, and lowering healthcare inequities by reviewing the body of research and successful case studies. Additionally, it talks on the financial benefits of funding preventive dental health initiatives, highlighting the possible long-term cost savings for patients as well as healthcare systems. The essay also discusses the societal ramifications, highlighting the ways that encouraging oral health education in schools can help to end the cycle of disparities in oral health, advance equity, and improve the standard of living. This article concludes by arguing in favor of oral health education be given priority in schools and presenting it as an important social investment that will pay off handsomely in the long run for the health of communities and people. Keywords: Oral Health Education; Schools; Social Investment.